2018
DOI: 10.1002/aoc.4535
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization, density functional theory (B3LYP) calculations, thermal behaviour, docking and antimicrobial activity of 4‐amino‐5‐(heptadec‐8‐en‐1‐yl)‐4H‐1,2,4‐triazole‐3‐thiol and its metal chelates

Abstract: Synthesis, structural characterization, density functional theory (B3LYP) calculations, thermal behaviour, docking and antimicrobial activity of 4-amino-5-(heptadec-8-en-1-yl)-4H-1,2,4-triazole-3-thiol and its metal chelatesThe structure of prepared triazole ligand 4-amino-5-(heptadec-8-en-1-yl)-4H-1,2,4-triazole-3-thiol and its coordination behaviour towards transition metal ions Ni (II), Co (II), Fe (III), Cd (II) and Cu (II) have been studied using magnetic measurements, elemental analyses and electronic, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Non‐polar hydrogen atoms were conjoined, and rotatable bonds were clarified. After the addition of fundamental hydrogen atoms, Kollman united atom type charges and salvation parameters the Auto Dock tools were applied . Determining van der Waals and electrostatic terms was performed by Auto Dock parameter set‐ and distance‐dependent dielectric functions, respectively.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Non‐polar hydrogen atoms were conjoined, and rotatable bonds were clarified. After the addition of fundamental hydrogen atoms, Kollman united atom type charges and salvation parameters the Auto Dock tools were applied . Determining van der Waals and electrostatic terms was performed by Auto Dock parameter set‐ and distance‐dependent dielectric functions, respectively.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…The 1 H-NMR and 13 2 ), 152.4 (triazole C-5), 167.9 (triazole C-3) ppm. The bands of SH and NH 2 are disappeared after ligand coordination to metal cations (Cd(II) and Zn(II)); which may be attributed to the sharing of these groups in Zn-HL and Cd-HL chelates formation [49,50].…”
Section: H-nmr and 13 C-nmr Of Ligand And Its Metal Chelatesmentioning
confidence: 99%
“…The complexation of drug to a metal ion promotes its activity and in some instances the complex has more biological activity than the corresponding drug [12]. The Traizole-Thiole ligands of N and S donor atoms in their structures are considered good chelating agents for the transition and non-transition metal cations [13]. The Traizole-Thiole metal chelates are of great interest due to their contributions [14] and their potential uses in applied sciences [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated to mutable capacity for the hydrogenbonding interaction by multi-central group's internal docking ligands. All proteins have inter hydrogen bonding [19][20][21]. The manner of interaction internal the docking molecules pocket was proved by three dimensional plots (Fig.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…The results revealed that most of the tested compounds exhibited good antibacterial and antifungal activities compared with the standards (Table 1). Iminocoumarine [22], thiazole and dihydropyridine skeletons present in compounds 3a, 5a and 6b respectively are considered to be the reason for their higher remarkable antimicrobial activity [19][20][21] (Table 1).…”
Section: For 5aez Protein the Amino Acids Hydrogen Bond And Energymentioning
confidence: 99%